Non-Newtonian flow in the process industries fundamentals and engineering applications - Chhabra, R. P.; Richardson, J. F. (John Francis) (Oxford ; Boston, MA : Butterworth-Heinemann, 1999)
Non-Newtonian materials are encountered in virtually all of the chemical and process industries and a full understanding of their nature and flow characteristics is an essential requirement for engineers and scientists involved in their formulation and handling. This book will bridge the gap between much of the highly theoretical and mathematically complex work of the rheologist and the practical needs of those who have to design and operate plants in which these materials are handled and processed. At the same time, numerous references are included for the benefit of those who need to delve more deeply into the subject. The starting point for any work on non-newtonian fluids is their characterisation over the range of conditions to which they are likely to be subjected during manufacture or utilisation, and this topic is treated early on in the book in a chapter commissioned from an expert in the field of rheological measurements. Coverage of topics is extensive and this book offers a unique and rich selection of material including the flow of single phase and multiphase mixtures in pipes, in packed and fluidised bed systems, heat and mass transfer in boundary layers and in simple duct flows, and mixing etc. An important and novel feature of the book is the inclusion of a wide selection of worked examples to illustrate the methods of calculation. It also incorporates a large selection of problems for the reader to tackle himself.
Non-Newtonian fluid behaviour; Rheometry for non-Newtonian fluids; Flow in pipes and conduits of non-circular cross-sections; Flow of multi-phase mixtures in pipes; Particulate systems; Heat transfer characteristics of non-Newtonian fluids in pipes; Momentum, heat and mass transfer in boundary layers; Liquid mixing.
Includes bibliographical references and index.
Keywords: Non-Newtonian fluids; Chemical engineering; Fluides non newtoniens; Electronic books